Revitalization Study of River Transportation as Urban Transportation Mode - Sidharta, Driaskoro Budi; Diani, Oktrianti; Sari, Dewi Kartika (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2020)
This study was conducted to find a revitalization model that will serve as a reference in the development of river transportation in the city of Bnajarmasin in the future. As is known, Banjarmasin has long played a strategic role in inter-island trade traffic, because it is located at the confluence of the Barito and Martapura rivers, which are broad and deep. So that the rivers can be navigated by large ships and the ships can dock as far as Banjarmasin City. Despite this the peculiarity of the number of rivers that are naturally used as transportation infrastructure, their role is gradually eroded by land transportation modes. Therefore, if the above conditions are not anticipated early on, the development of river transportation facilities and infrastructure will continue to undergo degradation physically and in function. This is certainly not beneficial for the future development of Banjarmasin City, because river transportation infrastructure is naturally available and the geography of Banjarmasin City still allows the river transportation system to be maintained and developed. The results of this study indicate that the revitalization of river transportation has the potential to be developed as an alternative urban transportation that is integrated with existing urban land transportation. because river transportation infrastructure is naturally available and the geography of Banjarmasin City still allows the river transportation system to be maintained and developed. The results of this study indicate that the revitalization of river transportation has the potential to be developed as an alternative urban transportation that is integrated with existing urban land transportation. because river transportation infrastructure is naturally available and the geography of Banjarmasin City still allows the river transportation system to be maintained and developed. The results of this study indicate that river transportation revitalization has the potential to be developed as an alternative urban transportation that is integrated with existing urban land transportation.